Nazi Medical Research in Neuroscience: Medical Procedures, Victims, and Perpetrators - Loewenau, Aleksandra; Weindling, Paul J (Canadian bulletin of medical history = Bulletin canadien d'histoire de la medecine, 2016)
Issues relating to the euthanasia killings of the mentally ill, the medical research conducted on collected body parts, and the clinical investigations on living victims under National Socialism are among the best-known abuses in medical history. But to date, there have been no statistics compiled regarding the extent and number of the victims and perpetrators, or regarding their identities in terms of age, nationality, and gender. "Victims of Unethical Human Experiments and Coerced Research under National Socialism," a research project based at Oxford Brookes University, has established an evidence-based documentation of the overall numbers of victims and perpetrators through specific record linkages of the evidence from the period of National Socialism, as well as from post-WWII trials and other records. This article examines the level and extent of these unethical medical procedures as they relate to the field of neuroscience. It presents statistical information regarding the victims, as well as detailing the involvement of the perpetrators and Nazi physicians with respect to their post-war activities and subsequent court trials.